LAMB WAVE-BASED STRUCTURAL MONITORING IN COMPOSITE LAMINATES - Писаренко, Олександр (SWorldJournal, 2025)
This study presents a numerical analysis of a quasi-isotropic layup, which serves as a working model for assessing the level of anisotropy in laminated composites. To achieve this, Lamb wave propagation was simulated in four distinct directions: 0°, 30°,